Understanding the quality‐of‐life experiences of older or frail adults following a new dens fracture: Nonsurgical management in a hard collar versus early removal of collar - Mia Closs; Paul Brennan; Angela Niven; Susan Shenkin; Helen Eborall; Julia Lawton (Wiley, 2024)
Abstract Introduction In the United Kingdom, fractures of the cervical dens process in older and/or frail patients are usually managed nonsurgically in a hard collar. However, hard collars can lead to complications and this management approach is now being questioned, with growing interest in maximising patients' short‐term quality‐of‐life. It is vital that patients' perspectives are considered; yet, there is a dearth of literature examining the aspect. To help inform wider decision‐making about use of collar/no collar management of dens fractures in older/frail people, we explored older/frail people's experience of the two management approaches and how they affected their perceived quality‐of‐life. Methods We interviewed older and/or frail adults with a recent dens fracture (aged ≥65 years or with a clinical frailty score of ≥5) or their caregiver. Participants were recruited from both arms of a clinical trial comparing management using a hard collar for 12 weeks (SM) with early removal of the collar (ERC) and were interviewed following randomisation and again, 12-16 weeks later. Data were analysed using a framework approach. Results Both participant groups (SM/ERC) reported substantial, negative quality‐of‐life (QoL) experiences, with the fall itself and lack of access to care services and information being frequent major contributory factors. Many negative experiences cut across both participant groups, including pain, fatigue, diminished autonomy and reduced involvement in personally meaningful activities. However, we identified some subtle, yet discernible, ways in which using SM/ERC reinforced or alleviated (negative) QoL impacts, with the perceived benefits/burdens to using SM/ERC varying between different individuals. Conclusion Study findings can be used to support informed decision‐making about SM/ERC management of dens fractures in older/frail patients. Patient or Public Contribution Public and patient involvement contributors were involved in the study design, development of interview topic guides and interpretation of study findings.